Seismic Response Reduction of Steel MRF Using SMA Equipped Innovated Low-damage Column Foundation Connection - Reza Jamalpour; Masood Nekooei; Abdolreza Sarvghad Moghadam (Civil Engineering Journal, 2017)
Connections in MRFs are the most important members and seismic behaviour is affected by function of beam column connections as well as column foundation connections. If the connections are able to provide the required ductility and efficiency against the seismic excitation, the seismic capacity of the MRF performed by these connections will be affected. SMAs have recently been used as a tool to dissipate energy in structures. So far, using of them for column foundation connections has been applied much less. In this paper, SMAs have been introduced and an innovated column foundation connection equipped with SMA has been suggested. Micro and macro behaviour of the connection has been studied and it was applied in sample MRF. Seismic response of the MRF under different earthquakes by equipping the connection with steels/SMAs bars have been studied and compared. Finally, results indicated that MRF with this connection showed proper seismic performance.